Long-term quality-adjusted survival following therapeutic bronchoscopy for malignant central airway obstruction. Issue 2 (25th September 2018) - Ong, Philip; Grosu, Horiana B; Debiane, Labib; Casal, Roberto F; Eapen, George A; Jimenez, Carlos A; Noor, Laila; Ost, David E
Abstract : Background: While therapeutic bronchoscopy has been used to treat malignant central (CAO) airway obstruction for >25 years, there are no studies quantifying the impact of therapeutic bronchoscopy on long-term quality-adjusted survival. Methods: We conducted a prospective observational study of consecutive patients undergoing therapeutic bronchoscopy for CAO. Patients had follow-up at 1 week and monthly thereafter until death. Outcomes included technical success (ie, relief of anatomic obstruction), dyspnoea, health-related quality of life (HRQOL) and quality-adjusted survival. Results: Therapeutic bronchoscopy was performed on 102 patients with malignant CAO. Partial or complete technical success was achieved in 90% of patients. At 7 days postbronchoscopy, dyspnoea improved (mean ∆Borg-day-7=−1.8, 95% CI −2.2 to −1.3, p<0.0001) and HRQOL improved (median prebronchoscopy 0.618 utiles, 25%–75% IQR 0.569 to 0.699, mean ∆utility-day-7+0.047 utiles, 95% CI +0.023 to 0.071, p=0.0002). Improvements in dyspnoea and HRQOL were maintained long-term. Compared with the prebronchoscopy baseline, HRQOL per day of life postbronchoscopy improved (mean ∆utility-long-term+0.036 utiles, 95% CI +0.014 to 0.057, p=0.002). Median quality-adjusted survival was 109 quality-adjusted life-days (QALDs) (95% CI 74 to 201 QALDs). Factors associated with longer quality-adjusted survival included better functional status, treatment-naïve tumour, endobronchial disease, less dyspnoea, shorter time from diagnosis to bronchoscopy, absence of cardiac disease, bronchoscopic dilation and receiving chemotherapy. Conclusions: Therapeutic bronchoscopy improves HRQOL as compared with baseline, resulting in approximately a 5.8% improvement in HRQOL per day of life. The risk-benefit profile in these carefully selected patients was very favourable. Trial registration number: Results; NCT03326570 .